2021
DOI: 10.1115/1.4050017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dispersant Concentration With Friction Modifiers and Anti-Wear Additives on the Tribofilm Composition and Boundary Friction

Abstract: To extend drain intervals and improve efficiency new engine oils with increased dispersant concentration and reduced viscosity are required. Low viscosity engine oils can increase the prevalence of boundary friction at low temperature and increase its severity at higher temperatures. As a result, combinations of organic and inorganic friction modifiers (FM) will be used to reduce boundary friction across a range of temperatures, also preventing damage to vehicle catalysts. This paper presents an experimental c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…Further study of organic friction modifiers and ZDDP has shown that the interaction of the two additives is dependent on the chemistry and concentration and can result in a positive (lower friction) [20,21] or negative [22] effects (higher friction). Umer et al [8] conducted experiments on ferrous samples which showed that organic friction modifiers and dispersants interfered with the formation of ZDDP tribofilms which is consistent with other literature [22][23][24][25][26]. Umer et al also discuss that ZDDP and inorganic friction modifier molybdenum dithiocarbamates (MoDTC) can work together to form a low friction tribofilms [27][28][29][30].…”
Section: Introductionsupporting
confidence: 66%
See 4 more Smart Citations
“…Further study of organic friction modifiers and ZDDP has shown that the interaction of the two additives is dependent on the chemistry and concentration and can result in a positive (lower friction) [20,21] or negative [22] effects (higher friction). Umer et al [8] conducted experiments on ferrous samples which showed that organic friction modifiers and dispersants interfered with the formation of ZDDP tribofilms which is consistent with other literature [22][23][24][25][26]. Umer et al also discuss that ZDDP and inorganic friction modifier molybdenum dithiocarbamates (MoDTC) can work together to form a low friction tribofilms [27][28][29][30].…”
Section: Introductionsupporting
confidence: 66%
“…The lubricants are described in in Table 2:. The remaining additive package remained consistent across the lubricants as shown in Table 3, the kinematic viscosity for all the candidate lubricants at 40°C is 38.3-40.3 cSt and at 100°C is 7.48-7.55 cSt [8]. Antioxidant Aminic octyl/butyl diphenylamine and phenolic ester (0.5wt%)…”
Section: Test Specimens Cylinder Liner and Oil Control Ringsmentioning
confidence: 73%
See 3 more Smart Citations